Health-related quality of life of dialysis patients during early COVID-19 lockdowns: a snapshot from a public hospital in Malaysia - Paneerselvam, Ganesh Sritheran; Goh, Khang Wen; Kassab, Yaman Walid; Farrukh, Muhammad Junaid; Goh, Bey Hing; Lua, Pei Lin; Hermansyah, Andi; Ming, Long Chiau (Frontiers in Medicine, 2023)
Background: End stage renal disease is the last stage of chronic kidney disease, and can affect the quality of life (QOL) of dialysis patients. The aim of this study was to assess this quality of life and examine its determinants. Methods: A cross-sectional survey involving patients on dialysis in a tertiary hospital was conducted from July 2020 to September 2020. Demographic data were collected using a predesigned questionnaire. QOL was measured using the 36-item KDQOL questionnaire, and statistical analysis was carried out using SPSS version 25. Results: Of the 108 patients, 59 were males and 49 females, and the mean age was 48.15  15.4 years old. The results showed that there was no significant difference in the mean score of all components of health-related quality of life in different types of dialysis. The demographic data, which included age, gender, ethnicity, marital status, education level, occupation and monthly income, did not significantly affect the QOL of dialysis patients. Patients with a dialysis duration of more than 5 years had a better QOL compared to other groups. Laboratory parameters such as low albumin and low hemoglobin showed a significant correlation with the health-related quality of life of dialysis patients. Conclusions: The quality of life among patients on dialysis was impaired, especially in terms of burden of the kidney disease. Hypoalbuminemia and anemia were the two factors that influenced QOL.